Alcohol, Self-Regulation and Partner Physical Aggression: Actor-Partner Effects Over a Three-Year Time Frame - Quigley, Brian M.; Levitt, Ash; Derrick, Jaye L.; Testa, Maria; Houston, Rebecca J.; Leonard, Kenneth E. (Frontiers in Behavioral Neuroscience, 2018)
The question of how individual differences related to self-regulation interact with alcohol use patterns to predict intimate partner aggression (IPA) is examined. We hypothesized that excessive drinking will be related to partner aggression among those who have low self-regulation. In addition, we explored the extent to which differences in self-regulation in one partner may moderate the relationship between alcohol use and partner aggression. A sample of married or cohabitating community couples (N = 280) ages 18-45 was recruited according to their classification into four drinking groups: heavy drinking in both partners (n = 79), husband only (n = 80), wife only (n = 41), by neither (n = 80), and interviewed annually for three years. IPA, drinking, and scores on measures of negative affect, self-control, and Executive Cognitive Functioning (ECF) were assessed for both members of the couple. The Actor Partner Interdependence Model (APIM) was used to analyze longitudinal models predicting the occurrence of IPA from baseline alcohol use, negative affect, self-control, and ECF. Actor self-control interacted with partner self-control such that IPA was most probable when both were low in self-control. Contrary to prediction, actors high in alcohol use and also high on self-control were more likely to engage in IPA. Partner alcohol use was predictive of actor IPA when the partner was also high in negative affect. Low partner ECF was associated with more actor IPA. These findings suggest that self-regulatory factors within both members of a couple can interact with alcohol use patterns to increase the risk for relationship aggression.